Synthesis, Antimicrobial and Anticancer Evaluation of N′-(Substituted Benzylidene)-2-(Benzo[d]oxazol-3(2H)-yl)acetohydrazide Derivatives - Rohilla, P.; Deep, A.; Kamra, M.; Narasimhan, B.; Ramasamy, K.; Mani, V.; Mishra, R. K.; Lim, S. M. (Drug Research, 2014)
A series of N′-(substituted benzylidene)-2-(benzo[d]oxazol-3(2H)-yl)acetohydrazide derivatives was synthesized and evaluated for its in vitro antimicrobial and anticancer activities. Antimicrobial activity results revealed that compound 12 was found to be the most potent antimicrobial agent. Results of anticancer study indicated that the synthesized compounds exhibited average anticancer potential. Compound 7 (IC50=3.12 µM) and compound 16 (IC50=2.88 µM) were found to be most potent against breast cancer (MCF7) cell lines. In conclusion, compound 12 and 16 have the potential to be selected as lead compound for the developing of novel antimicrobial and anticancer agents respectively.
Keywords: benzoxazoles; antimicrobial; anticancer